2006
DOI: 10.1038/ncpcardio0653
|View full text |Cite
|
Sign up to set email alerts
|

Therapy Insight: malignant primary cardiac tumors

Abstract: Benign cardiac tumors are resected with a high degree of success with modern cardiac surgical techniques. Malignant cardiac tumors, however, continue to pose a therapeutic challenge to cardiac surgeons and oncologists because of the technical difficulty involved in extensive cardiac resections and the aggressive biological nature of the tumors. The majority of malignant cardiac tumors are sarcomas and can be categorized as right heart sarcoma, left heart sarcoma or pulmonary artery sarcoma. Right heart sarcoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 20 publications
1
55
0
3
Order By: Relevance
“…25 Indeed, our multivariate model indicates malignant tumor histology is the most significant clinical predictor of mortality; however, we have also identified that younger patients tend to have particularly aggressive tumors. While some have advocated for highly aggressive surgical resection including cardiomyoplasty 26 and autotransplantation, 27 it is unclear whether either of these approaches result in superior survival outcomes. It is currently our clinical practice to pursue surgical resection when there is a likelihood of complete resection or if patients are severely symptomatic.…”
Section: Elbardissi Et Al Survival After Resection Of Primary Cardiacmentioning
confidence: 99%
“…25 Indeed, our multivariate model indicates malignant tumor histology is the most significant clinical predictor of mortality; however, we have also identified that younger patients tend to have particularly aggressive tumors. While some have advocated for highly aggressive surgical resection including cardiomyoplasty 26 and autotransplantation, 27 it is unclear whether either of these approaches result in superior survival outcomes. It is currently our clinical practice to pursue surgical resection when there is a likelihood of complete resection or if patients are severely symptomatic.…”
Section: Elbardissi Et Al Survival After Resection Of Primary Cardiacmentioning
confidence: 99%
“…cardiac explantation, ex vivo tumor resection, reconstruction and reimplantation) also has been described. 39,40 Our patient had stage IV metastatic melanoma that was deemed unresectable. Systemic treatment is the mainstay for disseminated malignant melanoma, while radiation and surgery play an adjunctive role.…”
Section: Discussionmentioning
confidence: 95%
“…However, the tumor metastasized to the vulva 1 month later and the patient succumbed due to local recurrence 13 months after diagnosis. It is hypothesized that adjuvant therapy may be indispensable to prevent local recurrence and distant metastasis, as well as provide improved survival, even in patients that have undergone complete resection (25).…”
Section: Discussionmentioning
confidence: 99%